All Days 2011
DOI: 10.2118/149108-ms
|View full text |Cite
|
Sign up to set email alerts
|

Automated Technology Improved the Efficiency of Directional Drilling in Extended Reach Wells in Saudi Arabia

Abstract: With the focus on continuous drilling optimization, a collaborative effort was implemented to analyze and assess drilling challenges encountered while drilling extended horizontal wells in the Khurais field in Saudi Arabia. The primary requirement was to enhance the efficiency of conventional downhole motor directional drilling systems in the challenging horizontal reservoir section. The Khurais field is located in a remote area in the central part of Saudi Arabia approximately 200 km from the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…This depth was determined by a typical torque and drag program [21,24,25]. The actual maximum depth was influenced by the surface maximum clockwise and counterclockwise torque [26]. It was found that the reactive torque of the mud motor was counteracted by the friction of the BHA, as presented in the Figure 5.…”
Section: Slider Drilling Technologymentioning
confidence: 98%
“…This depth was determined by a typical torque and drag program [21,24,25]. The actual maximum depth was influenced by the surface maximum clockwise and counterclockwise torque [26]. It was found that the reactive torque of the mud motor was counteracted by the friction of the BHA, as presented in the Figure 5.…”
Section: Slider Drilling Technologymentioning
confidence: 98%